2022
DOI: 10.1007/s11064-022-03776-w
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29c Inhibits TNF-α-Induced ROS Production and Apoptosis in Mouse Hippocampal HT22 Cell Line

Abstract: Recent reports have suggested that abnormal miR-29c expression in hippocampus have been implicated in the pathophysiology of some nervous system disease. However, many aspects underlying mechanism of miR-29c in regulating cellular functions in hippocampal neurons are not clear. In this study, HT22 cells were infected with lentivirus containing miR-29c or miR-29c sponge. Cell counting kit-8 (CCK8) and lactate dehydrogenase (LDH) assay kit were applied to evaluate cell viability and toxicity before and after TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Specifically, TNFα can induce ROS production in neurons via TNF receptor 1 (TNFR1) and subsequent NFκB-promoted gene expression of ROS-generating enzymes, such as iNOS and NOX2 . This has been demonstrated in HT-22 cell cultures, which further supports our use of the cell line to model the interaction between TNFα and OS …”
supporting
confidence: 54%
See 1 more Smart Citation
“…Specifically, TNFα can induce ROS production in neurons via TNF receptor 1 (TNFR1) and subsequent NFκB-promoted gene expression of ROS-generating enzymes, such as iNOS and NOX2 . This has been demonstrated in HT-22 cell cultures, which further supports our use of the cell line to model the interaction between TNFα and OS …”
supporting
confidence: 54%
“…38 This has been demonstrated in HT-22 cell cultures, which further supports our use of the cell line to model the interaction between TNFα and OS. 39 Nicotinamide riboside (NR) treatment in AD mouse models has been shown to prevent oxidative DNA damage, decrease measures of activated astrocytes and microglia, and inhibit the upregulation of proinflammatory pathways, including the release of TNFα. 35,40 In a model of vascular dementia, 8 weeks of daily intraperitoneal NAD + administration attenuated microglial activation and TNFα mRNA expression and blunted increased ROS in the hippocampus and cortex.…”
mentioning
confidence: 99%
“…Regulating microRNAs in the BBB may alleviate CIRI in animal and in vitro models with OGD/R. [8][9][10][11][12][13][14][15][16][17][18] In this study, we found microRNA-29a-5p decreased in astrocytes after OGD/R. Increased microRNA-29a-5p alleviated astrocyte injury and induced phenotype shifting of astrocytes.…”
Section: Discussionmentioning
confidence: 49%
“…MicroRNA-29a, microRNA-29b, and microRNA-29c decreased expression in CIRI. 1215 Knocking out microRNA-29a-5p increased microglia’s polarization and glutamate release, leading to an increase in infarct volume in the animal model of CIRI. 16 NADPH oxidase inhibitor reduced cerebral infarct volume and hemorrhagic transformation after mechanical reperfusion and increased the level of microRNA-29a-5p and microRNA-29c-3p in the rat ischemic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the expression changes of proinflammatory cytokines and anti-inflammatory cytokine in ischemic rats were studied at 6 and 24 h after reperfusion in this study. TNF-α is a key mediator in neuronal immunomodulatory system, and its abnormal expression plays an important role in various pathological processes (Lambertsen et al, 2012 ; Li B. et al, 2022 ). In the present study, very few TNF-α-positive cells were observed in the brain of the sham group, whereas TNF-α-positive cells was gradually upregulated in the ischemic penumbra of MCAO rats at 6 and 24 h after reperfusion, indicating that cerebral I/R resulted in increased expression of TNF-α.…”
Section: Discussionmentioning
confidence: 99%